Internalisasi Nilai Karakter dalam Perspektif Family Education pada Kurikulum Merdeka Belajar - Siti Nurhaliza; Fathullah Rusly; Farich Purwantoro (IBTIDA', 2023)
This study discusses family education in the independent learning curriculum. This study aims to determine the role and function of the values of character education from the perspective of family education independent learning curriculum. The author uses qualitative research methods by collecting data through existing sources, namely observation, interviews and documentation. Then do data analysis descriptive analysis method to draw conclusions from family education in the independent learning curriculum. The results of the study found that parental involvement in family education in Kramat sub-district, Banyuanyar sub-district is very important because there are several separate factors to build the character of the child. Start educating children by getting used to speaking politely, telling the truth, and setting an example for children. Therefore family education is very important to straighten out how children's character will be formed in the future.